2022
DOI: 10.5435/jaaos-d-21-01214
|View full text |Cite
|
Sign up to set email alerts
|

Industry Payments Among Editorial Board Members of Orthopaedic Journals: An Open Payments Analysis From 2014 to 2019

Abstract: Introduction: Although industry payments to physicians and surgeons remain a subject of controversy, relationships between industry and orthopaedic surgeons continue to grow. Notably, recent analyses have demonstrated significant increases in the rate and magnitude of payments among orthopaedic surgeons, despite the passing of the Physician Payments Sunshine Act in 2010. Given the concerns regarding how these relationships may affect the peer-review process, our analysis aimed to evaluate how payments among ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…There are limited data on reporting the editorial involvement of surgeons receiving industry payments, but studies have explored the financial relationships of editorial board members in certain journals. A 5-year analysis of editorial board members of orthopedic journals from 2014 to 2019 showed that nearly half of them received industry payments and an increasing trend was observed 23 . Kwee and Kwee 39 conducted a similar study on editors of imaging-related journals, which revealed that 41% of them have financial relationships and the financial COI disclosure were not publicly listed for 80% of editorial board members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are limited data on reporting the editorial involvement of surgeons receiving industry payments, but studies have explored the financial relationships of editorial board members in certain journals. A 5-year analysis of editorial board members of orthopedic journals from 2014 to 2019 showed that nearly half of them received industry payments and an increasing trend was observed 23 . Kwee and Kwee 39 conducted a similar study on editors of imaging-related journals, which revealed that 41% of them have financial relationships and the financial COI disclosure were not publicly listed for 80% of editorial board members.…”
Section: Discussionmentioning
confidence: 99%
“…One potential way is to analyze industry payments made to journal editors, given the fact that high-impact journals directly affect clinical practice. Samuel et al 23 observed high rates of industry payments among editorial board members in orthopedic journals, and similar findings were also seen in surgery and pathology journals 24,25 . Disclosing financial conflict of interest (COI) can promote research integrity, fair academic environment, and high-quality patient care, 26 thus knowing the rate of COI disclosure can also help us better understand medical ethical dilemmas.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…T he Open Payments database (OPD), a repository of industry transfers of value to physicians and hospitals, was established to facilitate transparency in health care. 1,2 Previous investigations examined industry transfers of value to plastic surgeons, identifying a degree of asymmetry and heterogeneity in industry engagement. 3 Nevertheless, payments to editorial board members of plastic surgery journals are poorly described.…”
mentioning
confidence: 99%
“…Only "general payments" (excluding research funding or payments) were assessed in our investigation because of concerns regarding the veracity of other payment types. 1 Transfers of value were inflation-adjusted to 2021 US dollars. Relevant data were collected in October and November of 2022.…”
mentioning
confidence: 99%